PUBLIC POLICY AND RELIGIOUS CONFLICT IN INDONESIA: THE CASE OF AHMADIYAH - Ari Ganjar Herdiansah (Universitas Padjadjaran, 2016)
among conflict cases is Ahmadiyah sect as struggling minorities who spreading their influence in the middle of Sunni Islam majority. The conflict escalated and manifest in violence during the 2000s. The government eventually enacted Joint Ministerial Decree (SKB 3 Menteri) in 2008, which constrained preaching activities of Ahmadiyah who being accused of heresy. However, the decree did not stop the violence against Ahmadiyah. The conflict of Ahmadiyah was not solely about the heresy that charged on the Ahmadis, but also involving the contest of values, ideas, and authority between the liberal and pluralist Muslim groups versus the conservative Muslim groups. While the policy embodies controversial state as it perpetuates majority domination as well as close opportunities for constructive dialogues between the conflicting parties, this article views it as a resolution to anticipate the worst scenario. Therefore, the state's role as a policy maker is stillneeded to actualize social order, national stability and keep the democratic life under control.